(untitled) (Research, Society and Development, 2024)
Introduction: The Singular Therapeutic Project (PTS), as defined by the National Humanization Policy Booklet of the Ministry of Health (2007), consists of a set of articulated therapeutic conduct proposals, applicable both individually and in a collective context. Objective: The present study aims to report the construction of the PTS for a patient assisted by the Primary Care network team, highlighting the strategies used and the results achieved. Methodology This project is a descriptive, observational study, with a qualitative approach, of the experience report type, carried out from April 2022 to August 2023, in a Basic Health Unit in Brusque. The elaboration methodology proposed by the National Humanization Policy Booklet of the Ministry of Health (2007) was followed, from which the PTS was constructed based on the recognition of the problem and the structuring of an intervention plan. Conclusion: The construction and application of the PTS resulted in significant improvements in the participant’s quality of life, especially by replacing insulin syringes with the application pen, simplifying their daily use. Furthermore, the experience demonstrated the success of the PTS in addressing and embracing the problems identified by the participant and their family, highlighting the effectiveness of this individualized treatment method in clinical practice.